Delignifikasi Ampas Tebu untuk Pembuatan Pulp Rendemen Tinggi dengan Proses Peroksida Alkali - Gustriani, Gustriani; Chadijah, St; Rustiah, Wa Ode (Al-Kimia, 2013)
Delignification is of lignin termination process with particular solvent that produce high yield the pulping. Alkaline peroxide process produces low kappa pulp. Bagasse contains 42-53% cellulose was used as a base material for pulping. Delignification of bagasse making of high yield pulp by the process of Peroxide Alkali has been done by varying the concentration of NaOH (4%, 5%, 6%, 7%, 8%) and length of cooking 1,5 hours in the temperature 121 °C and pressure 0,11 atm. The aim of the study is to obtain the optimum length of cooking the making of high yield of bagasse by process Peroxide Alkali. The method of the study is delignification with process of cooking using autoclave. The result of the study indicates that addition of concentration NaOH affects the pulp yield, number of permanganate and physical characteristic  of papers sheet. The highest yield pulp obtained is 53,97% observed at the concentration of NaOH 5%. Whereas, the lowest number of permanganate is 3, 98 obtained by adding the concentration of NaOH 8%.